Egyptian community pharmacies and self-care: Context, challenges and opportunities - Amr Youssef; Mohamed Ezzat Khamis Amin (Elsevier, 2023)
Community pharmacists are ideally positioned to play a key role in promoting self-care behaviors through judicious use of self-care interventions. As highlighted by the International Pharmaceutical Federation, supporting effective self-care is a key strategy for pharmacists to contribute to the sustainability of healthcare systems. Despite recent positive developments in national health policies, Egypt does not have a clear self-care strategy and policy. It also has no national programs focusing on community pharmacists and self-care, important components that future health policy initiatives should tackle. This commentary explores self-care policies, strategies, and developments in the Egyptian community pharmacy practice context. It describes national research, roles, and challenges within the current model of community pharmacy practice and education concerning self-care. It addresses opportunities that Egyptian community pharmacy has to support self-care in light of the anticipated changes in the Egyptian healthcare system. Noting that success in the delivery of self-care interventions within community pharmacies is associated with key factors, recommendations are suggested for community pharmacy stakeholders to address such factors guided by the World Health Organization's implementation considerations for individuals' health needs and self-care-related health system challenges (agency, availability, quality, cost, information, accessibility, utilization, social support, acceptability, and efficiency).